Persepsi Wisatawan terhadap Potensi Pariwisata Halal di Kota Jambi - Alfisyahri, Nuriah; Tessya Yunita Siregar; Robiatul Adawia; Nelly Rahmadani; Yuliana Safitri; Kurnia Permana (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze tourists' perceptions of the potential for halal tourism in Jambi City. The research sample consisted of 270 respondents who live or have visited tourist destinations in Jambi City. The data collection method used a questionnaire distribution. The results showed that the majority of respondents had visited various natural tourist attractions in Jambi City, with the Gentala Arasy Bridge being the main destination. In addition, the majority of respondents showed a willingness to support the development of halal tourism in Jambi City. These results provide an important picture for the development of halal tourism in the area. This study provides an important contribution to understanding tourists' perceptions of halal tourism in Jambi City. Thus, this study can be a reference for the government and tourism industry players in developing halal tourism in Jambi City and other areas in Indonesia. These findings can also be a basis for efforts to improve the quality and provision of tourism facilities that are friendly to Muslim tourists, as well as the need for support from the local government in realizing halal tourism. This study recommends the need for further research that is more detailed regarding the variables and aspects supporting halal tourism, so that it can provide a deeper contribution to the development of halal tourism in Indonesia.